Deformational plagiocephaly in normal infants: a systematic review of causes and hypotheses - Bock, Freia de; Braun, Volker; Renz-Polster, Herbert (Archives of disease in childhood, 2017)
Background Deformational plagiocephaly (DP) is one of the most prevalent abnormal ﬁndings in infants and a frequent reason for parents to seek paediatric advice. Objective To systematically review the literature and identify evidence and hypotheses on the aetiology and determinants of DP in otherwise healthy infants. Design Systematic keyword search in all major biomedical databases to identify peer-reviewed publications reporting (a) empirical research or (b) hypotheses on the aetiology of DP in healthy, term infants. 3150 studies published between 1985 and 2016 and containing relevant keywords were screened. In a two-pronged approach, results were summarised separately for the body of empirical work (22 studies) and the body of hypotheses (110 articles). Review ﬁndings Only a few empirical studies have examined risk factors in non-selected patient populations on a higher grade methodological level. The most commonly reported risk factors were: male gender, supine sleep position, limited neck rotation or preference in head position, ﬁrst-born child, lower level of activity and lack of tummy time. Agreement between empirical studies was poor for most exposures, including supine sleep position, tummy time and use of car seats. The articles reporting hypotheses on the aetiology of DP cover a wide ﬁeld of environmental and biological factors, but include little suggestions as to the potential inﬂuence of the everyday care environment of the baby. Conclusions and relevance The evidence on the aetiology of DP is fragmentary and heterogeneous. In addition, factors possibly relevant to the development of DP have not been appreciated in the scientiﬁc discussion.